Why Can They Learn So Well? The Multidimensional Impact of Parental Income Levels on Chinese Children’s Academic Achievement - Mengchen Li (SAGE Open)
Access to quality education is crucial for children from different social strata to achieve upward mobility. Understanding how family income differences translate into disparities in academic achievement is increasingly urgent amidst rigid social stratification. This study focuses on families from various income levels, exploring the relationship between parental income and children’s academic performance. Through in-depth interviews with parents and grounded theory analysis, it identifies four core categories: “economic resource endowment” “cultural capital” “emotional attitudes” and “social resources.” This study finds that high-income parents can provide high-quality educational resources, foster a positive family environment, offer ample emotional support, and integrate social networks. These factors contribute to their children’s academic development. Conversely, low-income parents often lack these advantages, hindering their children’s academic performance. However, the study reveals this relationship is not deterministic, as evidenced by cases of academic success in low-income families and underperformance in high-income ones. This underscores the importance of cultural capital and personal motivation alongside economic factors. This study constructs a multidimensional impact model of parental income levels on children’s academic achievement, revealing how income disparities create educational inequalities. Addressing these disparities requires collaborative efforts from the state, society, schools, and families to create a more equitable educational environment. This study enriches research on the factors influencing educational attainment and offers guidance for promoting educational equity.